The Impact of Profitability and Liquidity on Firm Value with Tax Avoidance as Intervening Variable of F&B Company - Anton Adventus Kacaribu; Jessica Winata (SAFE-Network, 2023)
This study aimed to analyze the effect of profitability and liquidity on firm value through tax avoidance as intervening variables. This research was conducted on the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange period 2018-2020. The total research data are 48 samples. Path analysis was used as an analytical technique with the SPSS version 25 software. The first structure of this research shows that both profitability and liquidity do not have a significant effect on tax avoidance, and the second structure shows that profitability has a significant effect on Firm Value. In contrast, liquidity has no significant effect on Firm Value. Tax avoidance has a significant effect on Firm Value. The direct effect of profitability on firm value is known to be 0.646, while the indirect effect is -0,071, which shows the direct is greater; therefore, indirectly, Tax Avoidance does not have a dominant effect on the firm value. The direct effect of liquidity on firm value is known to be -0.179, whereas the indirect effect of -0,049 is shown indirectly through Tax Avoidance has a dominant effect on the firm value.